2018
DOI: 10.3892/mmr.2018.8593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant vascular endothelial growth factor and translationally controlled tumor protein on 2‑hydroxyethyl methacrylate‑treated pulp cells

Abstract: Vascular endothelial growth factor (VEGF)-A is a potential signaling protein that may promote angiogenesis. VEGF also helps cells survive in stressfull or hazardous conditions. The present study aimed to compare the effect of VEGF with translationally controlled tumor protein (TCTP), an anti‑apoptotic protein in human dental pulp cells (HDPCs), following exposure to 2‑hydroxyethyl methacrylate (HEMA), which is a major residual monomer from resin restorative dental materials. Cell viability, alkaline phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The results showed that the plant-produced VEGF did not show any cytotoxic effect on HaCat cells in all the concentrations tested. This is consistent with the earlier reports which showed that recombinant VEGF [ 43 , 45 , 46 ] effectively promotes the growth of epithelial cells, oral primary cells and endothelial cells at low concentration.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that the plant-produced VEGF did not show any cytotoxic effect on HaCat cells in all the concentrations tested. This is consistent with the earlier reports which showed that recombinant VEGF [ 43 , 45 , 46 ] effectively promotes the growth of epithelial cells, oral primary cells and endothelial cells at low concentration.…”
Section: Discussionsupporting
confidence: 93%
“…The rFm-GST-TCTP protein has been reported to promote mineral deposition via activation alkaline phosphatase activity and expression of Dentin sialophosphoprotein (DSPP), dentin matrix protein 1 (DMP-1), and bone morphogenetic protein-2 (BMP-2) [48]. Besides, the rFm-Fortilin (FL) without glutathione S-transferase (GST)-in this studied was confirmed to promote cell mineralization.…”
Section: Plos Onementioning
confidence: 58%